Stationary beam full-field transmission helium ion microscopy using sub-50 keV He+: Projected images and intensity patterns - Mousley, Michael; Eswara, Santhana; De Castro, Olivier; Bouton, Olivier; Klingner, Nico; Koch, Christoph T.; Hlawacek, Gregor; Wirtz, Tom (Beilstein Journal of Nanotechnology, 2019)
A dedicated transmission helium ion microscope (THIM) for sub-50 keV helium has been constructed to investigate ion scattering processes and contrast mechanisms, aiding the development of new imaging and analysis modalities. Unlike a commercial helium ion microscope (HIM), the in-house built instrument allows full flexibility in experimental configuration. Here, we report projection imaging and intensity patterns obtained from powder and bulk crystalline samples using stationary broad-beam as well as convergent-beam illumination conditions in THIM. The He+ ions formed unexpected spot patterns in the far field for MgO, BN and NaCl powder samples, but not for Au-coated MgO. The origin of the spot patterns in these samples was investigated. Surface diffraction of ions was excluded as a possible cause because the recorded scattering angles do not correspond to the predicted Bragg angles. Complementary secondary electron (SE) imaging in the HIM revealed that these samples charge significantly under He+ ion irradiation. The spot patterns obtained in the THIM experiments are explained as artefacts related to sample charging. The results presented here indicate that factors other than channeling, blocking and surface diffraction of ions have an impact on the final intensity distribution in the far field. Hence, the different processes contributing to the final intensities will need to be understood in order to decouple and study the relevant ion-beam scattering and deflection phenomena.
Keywords: charging; helium ion microscopy; ion diffraction; ion scattering; transmission ion microscopy

(untitled) - Ward, B. W.; Notte, J. A.; Economou, N. P. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2006)

Surface Science Techniques - Bracco, G.; Holst, B. (Springer Berlin, 2013)

Helium Ion Microscopy - Hlawacek, G.; Gölzhäuser, A. (Springer, 2016)

(untitled) - Notte, J.; Ward, B.; Economou, N.; Hill, R.; Percival, R.; Farkas, L.; McVey, S.; Seiler, D. G.; Diebold, A. C.; McDonald, R.; Garner, C. M.; Herr, D.; et al. (AIP Conf. Proc., 2007)

(untitled) - Scipioni, L.; Sanford, C. A.; Notte, J.; Thompson, B.; McVey, S. (J. Vac. Sci. Technol., B: Microelectron. Nanometer Struct.–Process., Meas., Phenom., 2009)

(untitled) - Hlawacek, G.; Veligura, V.; Lorbek, S.; Mocking, T. F.; George, A.; van Gastel, R.; Zandvliet, H. J. W.; Poelsema, B. (Beilstein J. Nanotechnol., 2012)

(untitled) - Beyer, A.; Vieker, H.; Klett, R.; Meyer zu Theenhausen, H.; Angelova, P.; Gölzhäuser, A. (Beilstein J. Nanotechnol., 2015)

(untitled) - Joens, M. S.; Huynh, C.; Kasuboski, J. M.; Ferranti, D.; Sigal, Y. J.; Zeitvogel, F.; Obst, M.; Burkhardt, C. J.; Curran, K. P.; Chalasani, S. H.; Stern, L. A.; Goetze, B.; et al. (Sci. Rep., 2013)

(untitled) - Watt, F.; Chen, X.; Chen, C.-B.; Udalagama, C.; van Kan, J. A.; Bettiol, A. A. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2013)

(untitled) - Chen, X.; Udalagama, C. N. B.; Chen, C.-B.; Bettiol, A. A.; Pickard, D. S.; Venkatesan, T.; Watt, F. (Biophys. J., 2011)

(untitled) - Eder, S. D.; Reisinger, T.; Greve, M. M.; Bracco, G.; Holst, B. (New J. Phys., 2012)

(untitled) - Barr, M.; Fahy, A.; Martens, J.; Jardine, A. P.; Ward, D. J.; Ellis, J.; Allison, W.; Dastoor, P. C. (Nat. Commun., 2016)

(untitled) - Veligura, V.; Hlawacek, G.; van Gastel, R.; Zandvliet, H. J. W.; Poelsema, B. (Beilstein J. Nanotechnol., 2012)

(untitled) - Klingner, N.; Heller, R.; Hlawacek, G.; Facsko, S.; von Borany, J. (Ultramicroscopy, 2019)

(untitled) - Dowsett, D.; Wirtz, T. (Anal. Chem. (Washington, DC, U. S.), 2017)

(untitled) - Wirtz, T.; De Castro, O.; Audinot, J.-N.; Philipp, P. (Annu. Rev. Anal. Chem., 2019)

(untitled) - Veligura, V.; Hlawacek, G.; van Gastel, R.; Zandvliet, H. J. W.; Poelsema, B. (J. Lumin., 2015)

(untitled) - Vollnhals, F.; Audinot, J. N.; Wirtz, T.; Mercier-Bonin, M.; Fourquaux, I.; Schroeppel, B.; Kraushaar, U.; Lev-Ram, V.; Ellisman, M. H.; Eswara, S. (Anal. Chem. (Washington, DC, U. S.), 2017)

(untitled) - Notte, J. A.; Hill, R.; McVey, S. M.; Ramachandra, R.; Griffin, B. J.; Joy, D. C. (Microsc. Microanal., 2010)

(untitled) - Woehl, T. J.; White, R. M.; Keller, R. R. (Microsc. Microanal., 2016)

(untitled) - Wang, J.; Huang, S. H. Y.; Herrmann, C.; Scott, S. A.; Schiettekatte, F.; Kavanagh, K. L. (J. Vac. Sci. Technol., B: Nanotechnol. Microelectron.: Mater., Process., Meas., Phenom., 2018)

(untitled) - Zweifel, L. P.; Shorubalko, I.; Lim, R. Y. H. (ACS Nano, 2016)

(untitled) - D'Alfonso, A. J.; Forbes, B. D.; Allen, L. J. (Ultramicroscopy, 2013)

(untitled) - Kim, C.; Höfner, C.; Rabalais, J. W. (Surf. Sci., 1997)

(untitled) - Schüller, A.; Winter, H. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2009)

(untitled) - Melmed, A. J.; Smit, J. (J. Phys. E, 1979)

(untitled) - Pillatsch, L.; Wirtz, T.; Migeon, H.-N.; Scherrer, H. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2011)

SIMION (2019)

(untitled) - Berry, M. V.; Upstill, C. (Prog. Opt., 1980)

(untitled) - Bok, A. B.; le Poole, J. B.; Roos, J.; de Lang, H. (Adv. Imaging Electron Phys., 2017)

(untitled) - Kurdyumov, A. V.; Solozhenko, V. L.; Zelyavski, W. B. (J. Appl. Crystallogr., 1995)

(untitled) - Leszczynski, M.; Teisseyre, H.; Suski, T.; Grzegory, I.; Bockowski, M.; Jun, J.; Porowski, S.; Pakula, K.; Baranowski, J. M.; Foxon, C. T.; Cheng, T. S. (Appl. Phys. Lett., 1996)

(untitled) - Kiser, T.; Pauly, M. (EPFL Tech. Rep., 2012)
https://lgg.epfl.ch/publications/2012/caustics/caustic_art.pdf

Advances in Architectural Geometry 2012 - Kiser, T.; Eigensatz, M.; Nguyen, M. M.; Bompas, P.; Pauly, M. (Architectural Caustics — Controlling Light with Geometry, 2013)

(untitled) - Wu, J. S.; Weierstall, U.; Spence, J. C. H.; Koch, C. T. (Opt. Lett., 2004)

(untitled) - Kennedy, S. M.; Zheng, C. X.; Jesson, D. E. (Nanoscale Res. Lett., 2017)